Transformation of Hadith Teaching as an Effort to Revitalize Islamic Science in Pesantren - Tamjidnor; Suriagiri; Surawardi; Samdani; Fathul Amal; Khuzaini (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
This study aims to explore the method of teaching hadith with a chain of transmission applied at Pondok Pesantren Al Ihsan and its impact on preserving the Islamic scientific tradition. This article uses qualitative research with a case study approach. Data were collected through in-depth interviews, direct observation, and documentation of the data collected during the research and literature study of relevant sources. The results showed that the teaching of sanad hadith at Al Ihsan Islamic Boarding School was carried out systematically by prioritizing a deep understanding of the sanad to verify the validity of the hadith. In addition, this learning focuses on transferring textual knowledge and developing students' character and spiritual values. Students are invited to actively discuss, understand the historical context, and apply the hadith daily. The teaching method effectively preserves the tradition of hadith science, maintains the authenticity of Islamic teachings, and strengthens students' belief in the truth. This research contributes to the development of the study of Islamic religious education, especially in teaching hadith in Islamic boarding schools.